Kajian Kriteria Ramah Lingkungan Alat Tangkap Rawai Dasar Di Perairan Desa Lebetawi Kota Tual - Jacomina Tahapary; Erna Ahmoldar; Yanto Anwar; Abu S. Serang (Universitas Pattimura, 2025)
This study evaluates the operational effectiveness of bottom longline fisheries and analyzes the gear’s compliance with environmental-friendly criteria. Such assessment is essential for providing scientific insights into the potential impacts of fishing gear on the sustainability of fishery resources and the condition of aquatic habitats. The research was conducted in the waters of Lebetawi Village, Tual City, using survey methods combined with experimental fishing. Data collected included gear specifications, operational techniques, fishing ground characteristics, soak time, catch composition, and parameters related to environmental performance. All catches were identified to species level, counted, and measured for length and weight. The data were analyzed descriptively and qualitatively to characterize the fishing operation and evaluate the environmental performance of the gear. The results show that the effectiveness of bottom longline operations is influenced by water conditions, substrate type, bait suitability, and gear-setting speed. Based on the environmental-friendly assessment criteria, bottom longlines are classified as highly environmentally friendly, with scores ranging from 26 to 32. These findings demonstrate the potential of bottom longlines to be sustainably utilized in coastal fisheries.